Pengaruh Kualitas Audit dan Asimetri Informasi terhadap Manajemen Laba dengan Good Corporate Governance sebagai Variabel Moderasi - Tri Noor Hidayah; Putri Awalina; Fitria Magdalena Suprapto (Owner : Riset dan Jurnal Akuntansi, 2025)
The purpose of this study is to investigate the relationship between Audit Quality and Earnings Management, using GCG as a moderating variable. Additionally, this study will examine the influence of Information Asymmetry on Earnings Management, moderated by GCG. Moderated Regression Analysis is the research approach used to investigate the moderating effect of GCG and the correlation among variables. Twenty companies were selected as the sample using purposive sampling over a five-year period (2019–2023). The findings indicate that earnings management is significantly influenced by audit quality, and that GCG strengthens the effect of audit quality in reducing earnings management practices. However, GCG is found to be involved in regulating the relationship between Information Asymmetry and Earnings Management, although Information Asymmetry does not directly have a significant impact on Earnings Management. The importance of using GCG principles to enhance accountability and transparency in corporate financial management is emphasized by this study. The results indicate that audit quality has a negative effect on earnings management, while information asymmetry has a positive effect. Good Corporate Governance is proven to moderate the relationship between information asymmetry and earnings management. This study contributes to strengthening agency theory and corporate governance oversight practices.